(untitled) (Bangladesh Journal of Nuclear Medicine, 2025)
A thoracic ectopic kidney is the rarest kind of ectopic kidney, occurring in one out of every 15,000 cases. This renal anomaly is frequently diagnosed incidentally. We report a case of a man who had a non-visualized left kidney and later found out to be having a left thoracic kidney associated with a left Bochdalek hernia. Bangladesh J. Nuclear Med. 27(2): 305-309, 2024